1992
DOI: 10.1007/bf00229582
|View full text |Cite
|
Sign up to set email alerts
|

Studies on spice principles as antioxidants in the inhibition of lipid peroxidation of rat liver microsomes

Abstract: Polyunsaturated fatty acids (PUFA) are vulnerable to peroxidative attack. Protecting PUFA from peroxidation is essential to utilize their beneficial effects in health and in preventing disease. The antioxidants vitamin E, t-butylhydroxy toluene (BHT) and t-butylhydroxy anisole (BHA) inhibited ascorbate/Fe(2+)-induced lipid peroxidation in rat liver microsomes. In addition, a number of spice principles, for example, curcumin (5-50 microM) from turmeric, eugenol (25-150 microM) from cloves and capsaicin (25-150 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(69 citation statements)
references
References 29 publications
2
65
0
2
Order By: Relevance
“…These enzymes play an important role in the regulation of lipid peroxidation (Pulla Reddy & Lokesh 1992). Pulla Reddy and Lokesh (1992) observed that curcumin is capable of scavenging oxygen free radicals such as superoxide anions and hydroxyl radicals, which are important to the initiation of lipid peroxidation.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…These enzymes play an important role in the regulation of lipid peroxidation (Pulla Reddy & Lokesh 1992). Pulla Reddy and Lokesh (1992) observed that curcumin is capable of scavenging oxygen free radicals such as superoxide anions and hydroxyl radicals, which are important to the initiation of lipid peroxidation.…”
Section: Chemistrymentioning
confidence: 99%
“…These enzymes play an important role in the regulation of lipid peroxidation (Pulla Reddy & Lokesh 1992). Pulla Reddy and Lokesh (1992) observed that curcumin is capable of scavenging oxygen free radicals such as superoxide anions and hydroxyl radicals, which are important to the initiation of lipid peroxidation. Another article about curcuminoids as potent inhibitors of lipid peroxidation was described by Sreejayan Rao (1994), in which the authors showed that three curcuminoids were inhibitors of lipid peroxidation in rat brain homogenates and rat liver microsomes.…”
Section: Chemistrymentioning
confidence: 99%
“…An experiment using photodegradation on a larger scale made feasible the determination of the products formed after degradation by 1 H NMR spectra and HRMS-ESI + and ESI -analysis: thus 3,5-dimethoxybenzaldehyde (2), 3,5-dimethoxybenzoic acid (3) and Z and E isomers of dimethoxycinnamic acid (4a, 4b) were the major products, forming about 90% of the reaction mixture. Product 3 was formed by oxidation of 2, while both Z and E isomers of cinnamic acid derivatives were the result of photoisomerization, as confirmed by an independent experiment.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Its efficacy as a cancer chemopreventive agent is limited by its chemical and metabolic instability in buffers of neutral to alkaline pH. [5][6][7][8] When curcumin was incubated in 0.1M phosphate buffer and serum-free medium at pH 7.2, the initial degradation products ferulic acid and feruloyl methane were formed after only a few minutes, and feruloyl methane was then transformed by hydrolysis to the degradation products vanillin and acetone, their amounts increasing with incubation time.…”
Section: Introductionmentioning
confidence: 99%
“…Turmeric can lower lipid peroxidation by maintaining the activities of antioxidant enzymes like superoxide dismutase, catalase and glutathione peroxidase at higher levels. These enzymes play an important role in the regulation of lipidperoxidation (Pulla Reddy & Lokesh, 1992). Pulla Reddy and Lokesh (1992) observed that curcumin is capable of scavenging oxygen free radicals such as superoxide anions and hydroxyl radicals, which are important to the initiation of lipid peroxidation.…”
Section: Antioxidant Activitymentioning
confidence: 99%